Pertanggungjawaban Pidana Dugaan Perusakan Lingkungan Penyebab Terjadinya Banjir Di Sibolga (Studi Kasus Polres Sibolga) - Arifin Bernad Tampubolon; Fitri Rafianti; Henry Aspan (Judge : Jurnal Hukum, 2026)
Flood incidents occurring in Sibolga City are not merely influenced by extreme rainfall, but are also closely associated with the declining environmental conditions within surrounding ecological support areas, particularly in Tapanuli Tengah Regency. This situation gives rise to legal concerns regarding environmental law regulation and the extent to which criminal liability may be imposed for alleged environmental destruction contributing to flood disasters. This study aims to examine the legal framework concerning alleged environmental destruction related to flooding in Sibolga and to analyze the implementation of criminal liability for such actions. The research applies a normative-empirical legal method through statutory, conceptual, and case approaches. Data were collected through literature review, documentation studies, and interviews with relevant parties, then analyzed qualitatively using a juridical-analytical approach. The findings reveal that Indonesian environmental legislation generally provides a sufficient legal foundation to address activities causing environmental degradation. Nevertheless, the enforcement of environmental criminal law in flood-related cases in Sibolga continues to encounter several obstacles, particularly in proving causation, utilizing scientific environmental evidence, and establishing effective coordination among institutions. Accordingly, this study emphasizes the importance of strengthening scientific environmental evidence, improving inter-agency cooperation, and reinforcing the role of environmental criminal law as an instrument for environmental protection and disaster mitigation.